Necrotizing Enterocolitis: A Clinical Review on Diagnostic Biomarkers and the Role of the Intestinal Microbiota. Issue 2 (February 2015) - Niemarkt, Hendrik J.; de Meij, Tim G. J.; van de Velde, Mirjam E.; van der Schee, Marc P.; van Goudoever, Johannes B.; Kramer, Boris W.; Andriessen, Peter; de Boer, Nanne K. H.
Abstract : Abstract: Necrotizing enterocolitis (NEC) remains one of the most frequent gastrointestinal diseases in the neonatal intensive care unit, with a continuing unacceptable high mortality and morbidity rates. Up to 20% to 40% of infants with NEC will need surgical intervention at some point. Although the exact pathophysiology is not yet elucidated, prematurity, use of formula feeding, and an altered intestinal microbiota are supposed to induce an inflammatory response of the immature intestine. The clinical picture of NEC has been well described. However, an early diagnosis and differentiation against sepsis is challenging. Besides, it is difficult to timely identify NEC cases that will deteriorate and need surgical intervention. This may interfere with the most optimal treatment of infants with NEC. In this review, we discuss the pathogenesis, diagnosis, and treatment of NEC with a focus on the role of microbiota in the development of NEC. An overview of different clinical prediction models and biomarkers is given. Some of these are promising tools for accurate diagnosis of NEC and selection of appropriate therapy. Abstract : Article first published online 29 September 2014.